A VOCAL SKILL LESSON PLAN FOR THE YOUNG STUDENT WITH THE PRONUNCIATION AND BREATHING PROBLEMS - Janaporn, Pornchand; Tayrattanachai, Nion; Pokaratsiri, Duangruthai (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2024)
This research is a AB single-case design methodology. The objective was to develop a vocal skill lesson plan for the young student with pronunciation and breathing problems by using adaptation method. Research participant was a 6 years old student with pronunciation and breathing problems. The tools used in the research were vocal lesson plan for young student with pronunciation and breathing problems, evaluation rubric chart and after class teaching record. The analysis result found that student has higher score on intervention: B than baseline: A in every topic. On baseline: A student got 0-2 score in each topic and on intervention: B student got 3-4 score. The result and after class teaching record showed that lesson plan can help student improve skill and problems, and adaptation method is suitable for developing an individual lesson plan.